2011
DOI: 10.1016/j.livsci.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Oestrous intensity is positively associated with reproductive outcome in high-producing dairy cows

Abstract: his study tested whether strong oestrus symptoms are linked to low lameness score, acceptable pregnancy and calving rates in heifers and first parity dairy cows with a high genetic potential for milk production. In a single Swedish nucleus herd for genetic selection and testing, oestrous intensity was determined by detailed observations of 67 females, balanced in terms of age and breed (37 heifers and 30 first-parity cows; 32 Swedish Red cows and 35 Swedish Holsteins). Animals were inseminated with semen of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…An increasing relationship between OI (one to five) and CR (24-54%) was found (Figure 4). This finding is in agreement with Garcia et al (2011), who reported higher pregnancy and calving rates with a more intensive oestrus. There was a marked increase in CR between scores two and three (28% and 40%), where score two was based on oestruses with only local and secondary symptoms, such as anxiety, and score three Table 3.…”
Section: Discussionsupporting
confidence: 92%
“…An increasing relationship between OI (one to five) and CR (24-54%) was found (Figure 4). This finding is in agreement with Garcia et al (2011), who reported higher pregnancy and calving rates with a more intensive oestrus. There was a marked increase in CR between scores two and three (28% and 40%), where score two was based on oestruses with only local and secondary symptoms, such as anxiety, and score three Table 3.…”
Section: Discussionsupporting
confidence: 92%
“…To overcome this problem, cervix needs to *Corresponding author:-E-mail: nazmun_naher_bau@yahoo.com be relaxed to allow deeper penetration by the inseminating pipette through the cervical folds (Leethongdee, 2011) or the cervix can be bypassed through laparoscopic artificial insemination (LAPAI) (Hiwas et al, 2009). Intensity of oestrus and Vaginal Electrical Resistance (VER) are considered as important factors influencing pregnancy rate (Kozdrowski et al, 2006;Garcia et al, 2011). The main objectives of this study were to develop the TCAI through increasing cervical penetration depth and improve LAPAI to increase pregnancy rate, and to determine effects of induced oestrus intensity and vaginal electrical resistance (VER) on pregnancy rate of indigenous ewes using AI with frozen semen.…”
Section: Introductionmentioning
confidence: 99%
“…Lameness also decreases fertility (Alawneh et al, 2011;Morris et al, 2011) with the odds of pregnancy being reduced 5.1 times and that of calving reduced 3.5 times (Garcia et al, 2011).…”
Section: Impact Of Lameness Mastitis Metabolic and Reproductive Dismentioning
confidence: 99%